Development of a Core Outcome Set for the Benefits and Adverse Events of Acute Heart Failure in Clinical Trials of Traditional Chinese Medicine and Western Medicine: A Study Protocol - Qiu, Ruijin; Han, Songjie; Wei, Xuxu; Zhong, Changming; Li, Min; Hu, Jiayuan; Wang, Pengqian; Zhao, Chen; Chen, Jing; Shang, Hongcai (Frontiers in Medicine, 2021)
Aims The aim of this research is to identify a minimum set of benefits and adverse events for patients with acute heart failure (AHF) among different stakeholders in clinical trials of traditional Chinese medicine and Western medicine. Methods and analysis First, we will develop a preliminary long list of outcomes that include benefits and adverse events/reactions via three steps: (i) systematic reviews of efficacy and safety outcomes for clinical trials of AHF; (ii) drugs included in National Medical Insurance Catalog and the National Essential Medicines Catalog will be collected and extracted safety outcomes from Package Inserts; (iii) patients’ semi-structured interviews will be carried out to add new viewpoints to the list. Second, after merging outcomes and grouping them under different outcome domains, questionnaires for health professionals and the patients will be developed separately. Then two rounds of Delphi survey for health professionals as well as survey for patients will be carried out. Third, different stakeholders will discuss and determine the final core outcome set (COS) for AHF in consensus meeting. Ethics and dissemination The entire project has been approved by the Ethics Committee of the main institution. After the final COS developed, it will be published and disseminated in conferences. Trial registration number This study is registered with the Core Outcome Measures in Effectiveness Trials database as study 1566 (available at: http://www. cometinitiative.org/ studies/ details/ 1566).